THE IMPACT OF FINANCIAL TECHNOLOGIES ON THE BANKING SECTOR - Ergashev Aziz Avazkhon ugli (Scholars Digest Publishing, 2023)
The banking sector has undergone a significant transformation in recent years due to the advent of financial technologies (fintech). This article aims to explore the impact of fintech on the banking sector, focusing on three key areas: customer experience, operational efficiency, and competition. Firstly, fintech has revolutionized the way customers interact with banks, offering more personalized and convenient services through mobile banking apps and online platforms. Secondly, fintech has enabled banks to streamline their operations and reduce costs through automation and digitization. Finally, fintech has disrupted traditional banking models by enabling new entrants to enter the market and compete with established players. The article concludes that while fintech presents both opportunities and challenges for the banking sector, banks must embrace these technologies to remain competitive in an increasingly digital world.
Keywords: Fintech; Banking; Disruptionl; Innovation; Digitalization.